1991
DOI: 10.1266/jjg.66.635
|View full text |Cite
|
Sign up to set email alerts
|

Mutability of constitutive heterochromatin (C-bands) during eukaryotic chromosomal evolution and their cytological meaning.

Abstract: A quantitative analysis of the alterations of constitutive heterochromatin in eukaryotic chromosomal evolution was attempted using the accumulated C-banding data available for mammals, amphibians, fish, ants, grasshoppers, and plants. It was found that these eukaryotes could be classified into two types by their C-banding patterns: 1) Type I included mammals, fish, and ants, and 2) Type II included amphibians, grasshoppers, and plants. C-bands were rather scarce in Type I eukaryote chromosomes and were found a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
93
0
2

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(105 citation statements)
references
References 77 publications
10
93
0
2
Order By: Relevance
“…This C-banding pattern was very interesting due to the small amounts of heterochromatin it showed. This feature is consistent with the hypothesis of chromosomic differentiation via Robertsonian fusions, because it has been postulated that this kind of chromosomic changes usually involves the loss of centromeric heterochromatin in the acrocentric chromosomes that take part in the transformation (IMAI 1991). It has been determined that this situation in similar in other genera of South American cricetine rodents such as Holochilus (FREITAS et al 1983: SANGINES andAGUILERA 1991).…”
Section: Methodssupporting
confidence: 82%
“…This C-banding pattern was very interesting due to the small amounts of heterochromatin it showed. This feature is consistent with the hypothesis of chromosomic differentiation via Robertsonian fusions, because it has been postulated that this kind of chromosomic changes usually involves the loss of centromeric heterochromatin in the acrocentric chromosomes that take part in the transformation (IMAI 1991). It has been determined that this situation in similar in other genera of South American cricetine rodents such as Holochilus (FREITAS et al 1983: SANGINES andAGUILERA 1991).…”
Section: Methodssupporting
confidence: 82%
“…Another aspect to be considered is the model proposed to explain the karyotype evolution of Meliponini. This model proposes that centric fission events would be responsible for the increased number of chromosomes and accumulation of heterochromatin at the breaking points to re-establish the fission regions (Imai 1991;Imai et al 1988). If chromosomes have evolved according to this model, another hypothesis to explain the similarity between heterochromatic regions would involve the amplification of a common region found in all chromosomes of each species.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent changes in the chromosome number would have been the result of Robertsonian rearrangements. In contrast, data published by Pompolo (1992), Rocha et al (2003) and Gomes (1995) suggested that the karyotype evolution of bees and wasps follows the same cycle of changes proposed by Imai et al (1988), Imai and Taylor (1989), Imai (1991) and Hoshiba and Imai (1993) for different groups. Hoshiba and Imai (1993) suggested karyotype evolution according to the minimum interaction theory, which assumes that the main mechanisms involved in this process favor an increase in the chromosome number by centric fission, resulting in a reduction of size and, consequently, of a physical interaction between chromosomes during meiosis.…”
mentioning
confidence: 84%
“…According to the nomenclature proposed by Imai (1991), the diploid karyotype consists of one metacentric chromosome pair which is very long compared to the remaining karyotype, two acrocentric pairs and 13 pseudoacrocentric pairs, differing little in size (Figure 1 A and B).…”
mentioning
confidence: 99%